Being the ‘med reg’: an exploration of junior doctors’ perceptions of the medical registrar role - Fisher, James M.; Garside, Mark J.; Brock, Peter; Gibson, Vicky; Hunt, Kelly; Wyrko, Zoe; Gordon, Adam L. (Royal College of Physicians of Edinburgh, 2017)
The role of the medical registrar is a challenging one and is acknowledged as being a disincentive to a career in medicine for some junior doctors. We set out to build a broader understanding of the role through exploration of Foundation Doctors’ and Core Medical Trainees’ perceptions of the role. Data, gathered from focus groups, were analysed using a framework approach. Six key themes were identified, which were grouped under the headings ‘perceptions of the medical registrar role’ and ‘transition into the role’. Our work builds on existing literature to inform a deeper understanding of how junior doctors perceive the medical registrar role. In light of our findings we offer suggestions on possible training initiatives to tackle the issues identified. We also highlight positive perceptions of the role and emphasise the key ambassadorial role that current medical registrars have in relation to attracting tomorrows’ medical registrars to the specialty.